PENGEMBANGAN MEDIA 3 DIMENSI DALAM PEMBELAJARAN PAI - Batubara, Alwi Umar; Ayuni, Audy; Ramadhansyah, Frezzy; Kharisma Sitorus, Nur Ikhsan; Sari Rangkuti, Rini Antika; Abdillah Hasibuan , Zainuddin (Pimpinan Cabang Muhammadiyah Kramat Jati, 2023)
: This research aims to determine the development of three-dimensional media in PAI learning. The development of three-dimensional media in PAI learning is studied using qualitative research where the data and analysis sources are books and reading literature related to three-dimensional media. Apart from that, the arguments which are the basis for the use and development of three-dimensional media are also included. In general, three-dimensional media is a tool used in the learning process in the form of space, which has length, width and height with volume. In PAI learning, three-dimensional media is used to support the learning process, by paying attention to the selection of learning media that is right on target according to students' needs. Apart from that, the development of PAI learning media must also pay attention to Islamic principles and sharia in the process of creating and developing it. Therefore, teachers must be able to think creatively and be active in developing PAI learning media that is appropriate to the learning process, in line with current developments and utilizes developing technology.